Hydrogen production from biogas reforming : An overview of steam reforming, dry reforming, dual reforming, and tri-reforming of methane - Pham Minh, Doan; Siang, Tan Ji; Vo, Dai Viet N.; Phan, Thanh Son; Ridart, Cyrille; Nzihou, Ange; Grouset, Didier (Elsevier, 2018)
Green hydrogen can be produced from biogas as a renewable resource using a multistep process, including mainly biogas reforming, water-gas-shift reaction, and hydrogen separation. This chapter is focused on different methane reforming processes: steam reforming, dry reforming, dual reforming, and tri-reforming. In fact, only steam methane reforming (SMR) has been commercialized, but it is well known as a highly energy intensive process. Thus, alternative processes, such as dry, dual, and tri-reforming, are being developed. These solutions are significantly interesting for biogas reforming because of its high carbon dioxide content, which can be used as an oxidant. For each process, different aspects will be presented, including: thermodynamic equilibrium, process at industrial scale or research laboratory development, kinetic models, and mechanistic study.